effectiveness of the RADEC learning model on the numerical ability of madrasah tsanawiyah students - Nadia Oktavia; Aan Subhan Pamungkas (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
Numeracy skills are essential for junior high school students in the 21st century. The RADEC (Read, Answer, Discuss, Explain, Create) model is appropriate for implementation. This research aims to examine the effectiveness of the RADEC learning model in improving the numeracy skills of junior high school students. The research utilizes a quasi-experimental method with a nonequivalent control group design. The subjects of this research are male and female students in Madrasah Tsanawiyah Negeri (MTsN) 1 Pandeglang, with the population consisting of all seventh-grade students in MTsN 1 Pandeglang during the even semester of the academic year 2022/2023. The sample includes two classes determined purposively, with class VII A as the control group and class VII E as the experimental group. The instrument used in this research is a numeracy skills test. The research findings indicate that the improvement in numeracy skills of students using the RADEC model is considered better than that of students using the problem-based learning model. In conclusion, the RADEC learning model is more effective in enhancing students' numeracy skills than the problem-based learning model.